Writing Skill Using Learning Log and Conferencing Technique: Collaborating Principles of Constructivism Philosophy for Non-English Department Student - Retma Sari; Teguh Setiawan (Universitas Tidar, 2022)
Based on constructivism philosophy, this study investigates to find the learning technique of writing, in order to substitute the conventional technique of writing to improve writing skill. Log and conferencing technique has many advantages to reach the needs. In English syllabus of Animal Science program at Universitas Tidar, it is emphasized to apply writing in scientific form, so the use of grammar, diction and idea must be done appropriately. The major discussion is what learning log and conferencing is and how to apply it also how effective the learning model with this technique in improving writing skills for non-English Department students. Specific study has been given to make comfortable the relation and communication between teacher and student gradually and regularly. To get this aim, this study concerns with log and conferences techniques to animals science and using the new steps on writing learning style. The data from students and lecturers were collected and analyzed. Data analysis shows that the conferences appeared by variety of topics such as writing aspect, learning habits and English writing ability of each student. Second, the lecturer used varieties of approaches to communicate with each student in writing learning using learning log. Finally, the conferences contribute to a deliberative process critical to the process of learning to write. The students found conversations with the instructor helpful in their subsequent revisions whereas the instructor gained a better understanding of students’ difficulties in writing.